DEVELOPMENT OF PICTURE STORYBOOK MEDIA (BCB) TO IMPROVE THE BEGINNING READING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Dayang Lidya Fitriah,; Zunidar, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract This study aims to develop learning media in the form of Drawing Story Books (BCB) that effectively improve the reading skills of the third-grade students of SD Negeri 1 Kuning, Southeast Aceh. The research method used is research and development with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The study subjects were students of SD Negeri 1 Kuning, Southeast Aceh, consisting of 20 students. Instruments used in this study were validity instruments, practical instruments, and efectivity instruments. The developed media was validated by experts and tested on students for a validation score indicating that the media was feasible. The study's results showed students' enthusiasm for the BCB media, which improved their reading skills. Student evaluation resulted in a response score indicating that this media is appropriate and interesting. This study also revealed that using bright colors, attractive illustrations, and Canva-based designs effectively attracted students' attention and increased reading motivation. The media developed meets Indonesian language learning standards and can be used as a learning aid inside and outside the classroom.